2003
DOI: 10.1021/nl034217d
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Growth of Single-Crystal Metal Nanowires via a Two-Dimensional Nucleation and Growth Mechanism

Abstract: Metallic nanowires (Au, Ag, Cu, Ni, Co, and Rh) with an average diameter of 40 nm and a length of 3-5 μm have been fabricated by electrodeposition in the pores of track-etched polycarbonate membranes. Structural characterizations by transmission electron microscopy (TEM) and electron diffraction showed that nanowires of Au, Ag, and Cu are single-crystalline with a preferred [111] orientation, whereas Ni, Co, and Rh wires are polycrystalline. Possible mechanisms responsible for nucleation and growth for single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
355
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(378 citation statements)
references
References 28 publications
9
355
0
2
Order By: Relevance
“…This can be produced by plasma or vacuum deposition of a metal layer on one side of the membrane (25) and requires that the membrane film be robust enough to tolerate this kind of manipulation. The thickness of the conductive layer is typically 100-1000 nm (45)(46)(47). The metal which produces the conductive layer can be the same or different from the one that will provide the final template structure.…”
Section: Electrochemical Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be produced by plasma or vacuum deposition of a metal layer on one side of the membrane (25) and requires that the membrane film be robust enough to tolerate this kind of manipulation. The thickness of the conductive layer is typically 100-1000 nm (45)(46)(47). The metal which produces the conductive layer can be the same or different from the one that will provide the final template structure.…”
Section: Electrochemical Depositionmentioning
confidence: 99%
“…Metal Deposition potentiostatic conditions. In the case of track-etched PC, it was recently shown that the addition of 1-2% gelatin to the plating solution improves the wettability of the nanoporous membrane, thus improving the reproducibility of the electrodeposition step (45,(48)(49)(50).…”
Section: Electrochemical Depositionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] Meanwhile experimentally, twins, a class of planar defects, are observed most often in single-crystal metal ͑copper, silver, and gold͒ nanowires with a ͓111͔ growth orientation. 15,16 Because twin boundaries ͑TBs͒ in nanowires will strongly affect the physical properties of nanowires, it is of great significance to investigate the details of twin structures and their roles in metal nanowires. Until now, there are still some key issues about twin related deformation which are not quite clear and need fundamental understanding.…”
mentioning
confidence: 99%
“…15,16 The initial configuration of the twinned nanowires is constructed by repeating ⌺3 coherent twins in the ͗111͘ axis orientation. 18 Four samples are prepared for the simulations.…”
mentioning
confidence: 99%
“…Thus, the electrodeposition from silver complex solutions is preferred. Previous research shows that the deposition of silver nanowires from solutions formed principally with a diversity of additives: acetaldehyde [12], cyanide [10], potassium thiocyanate [8] and nitric acid [2]. Some of these solutions are toxicity, or the pH values are too low or too high, so they are not applicable for AAO template because the solubility process of amorphous alumina membranes begins at pH < 5 and pH > 8.2 [13].…”
Section: Silver Nanowire Growth Mechanismmentioning
confidence: 99%